OPODATKOWANIE UDZIAŁU W ZYSKACH SPÓŁKI OSOBOWEJ NA GRUNCIE UMÓW O UNIKANIU PODWÓJNEGO OPODATKOWANIA - Redakcja (Wydział Prawa i Administracji UAM, 2005)
The subject of the paper are the taxation rules of a partner’s income earned in a partnership established in another state. The paper focuses predominantly on the specific dogmatic problems having their origin in the differences resulting from domestic tax laws of member states who are parties of respective bilateral tax treaties concerning the treatment of a partnership as a subject to income taxation. The recommendations of the OECD that the state which applies the credit method is obliged to give credit for the source tax levied on partnership may be considered as convincing. As of 1 January 2005 the Polish internal tax considers a foreign partnership as a subject to taxation if the tax law of the state where such a partnership is registered treats it as a legal person.
TAXATION OF THE INCOME RESULTING FROM THE PARTICIPATION IN A PARTNERSHIP IN THE LIGHT OF THE PROVISIONS OF DOUBLE TAXATION AVOIDANCE AGREEMENTS